Advanced diffusion weighted imaging of the prostate: Comparison of readout-segmented multi-shot, parallel-transmit and single-shot echo-planar imaging. Issue 130 (September 2020) - Klingebiel, M.; Ullrich, T.; Quentin, M.; Bonekamp, D.; Aissa, J.; Mally, D.; Arsov, C.; Albers, P.; Antoch, G.; Schimmöller, L.
Highlights: Readout-segmented multi-shot echo-planar imaging (rs-EPI) and parallel transmit (ptx)-EPI showed a significantly higher contrast intensity between prostate cancer (PCa) and benign PZ or TZ compared single-shot (ss)-EPI. Subjective IQ was significantly higher for rs-EPI. Single PCa lesions could only be recognized and correlated on rs-EPI. Abstract: Purpose: This study evaluates objective and subjective image quality (IQ) of three different diffusion weighted imaging (DWI) sequences in prostate MRI at 3.0 Tesla within the same patients. Method: Thirty-six consecutive patients (70 ± 8 years) with multi-parametric prostate MRI (mp-MRI; 3 T) and subsequently verified prostate cancer (PCa) by targeted plus systematic MR/US-fusion biopsy from 03/2016 to 12/2017 were included. Readout-segmented (rs) multi shot echo-planar imaging (EPI), parallel transmit (ptx) EPI, and single-shot (ss) EPI with b-values of 0, (500, ) 1, 000 s/mm² and calculated b1, 500 were prospectively acquired of every patient. Signal intensities (SI) of PCa and benign tissue (peripheral and transition zone; PZ and TZ) in ADC, b1, 000, and calculated b1, 500 images were analyzed. Endpoints were signal-to-noise ratio (SNR), contrast-to-noise ratio (CNR), and subjective IQ on a 5-point scale by two blinded readers. Results: For ss-EPI ADC, b-values of 1, 000, and calculated 1, 500 s/mm² images showed a higher SNR compared to rs-EPI and ptx-EPI (p < 0.01). CNR of PCa and benign tissue was significantly higher for rs-EPI in high b value images compared to ptx-EPI and ss-EPI (p < 0.01). Subjective IQ was significantly higher for rs-EPI (p < 0.01). Significantly higher ADC reduction combined with signal increase on high b value images for PCa compared to the surrounding healthy tissue in PZ and TZ (PCa contrast intensity) was detected for rs-EPI (p < 0.01). Single PCa lesions could only be recognized and correlated on rs-EPI. Conclusions: Rs-EPI and ptx-EPI were superior to ss-EPI regarding contrast intensity of PCA, but inferior regarding SNR. Subjective imaging parameters were superior for rs-EPI. Especially rs-EPI, but also ptx-EPI might improve and faciliate prostate cancer detection, rs-EPI at the expense of a longer acquisition time.